Conjuring Sacred Space in Gulf Coast Cities. (1st February 2018) - Lipsitz, George
Abstract: In the midst of the disarray and divisiveness that accompanies the pervasive presence of poverty, political powerlessness, and racism, working class black artists and activists in the underscapes of New Orleans and Houston deploy creative place making to transform urban sacrifice zones into sacred spaces. Staging festive street parades and performances in New Orleans and converting abandoned row houses into a collectively created work of living sculpture in Houston constitute acts of conjuring and creative place making. By telling alternative and oppositional stories about the history of these cities and their people, artistic projects turn places of containment and confinement into venues for envisioning and enacting new kinds of physical and psychological mobility. They counter the harsh realities in impoverished communities by honoring the deceased through performances that figuratively bring them back to life, honor departed ancestors and summon their spirits, and offer resilient love as an antidote to social death.